Strategic and Financial Performance Implications of Global Sourcing Strategy: A Contingency Analysis - Murray, Janet Y.; Kotabe, Masaaki; Wildt, Albert R. (Journal of International Business Studies, 1995)
Using a contingency model of global sourcing strategy, this study investigated the moderating effects of sourcing-related factors on the relationship between sourcing strategy and a product's strategic and financial performance. The results lent some support to the contingency model of global sourcing strategy in that product innovation, process innovation and asset specificity were significant moderator variables for financial, but not strategic, performance. However, the results provided no support for bargaining power of suppliers and transaction frequency as moderator variables. In other words, in achieving high financial performance for a product, whether a particular sourcing strategy should be used for a particular product depended on the levels of product innovation, process innovation and asset specificity.